Historical biogeography of a new antitropical clade of temperate freshwater fishes. (16th May 2014) - Chen, Wei‐Jen; Lavoué, Sébastien; Beheregaray, Luciano B.; Mayden, Richard L.; Riddle, Brett
Abstract Aim Any discovery of new biogeographical pattern in landlocked animals may challenge hypotheses that account for the evolution of intercontinental faunas. In this study, we examined the evolutionary origin and historical biogeography of temperate, freshwater perch‐like fishes within a molecular phylogenetic framework. Location Temperate Eastern Eurasia, the Americas and Australia. Methods Data from five nuclear markers obtained from 15 targeted species and a broad sampling of percomorphs were assembled to investigate their phylogeny and historical biogeography. We (1) applied a fossil‐calibrated Bayesian reconstruction to provide a phylogenetic time‐scale for the diversification of the taxa, (2) inferred the evolution of habitat preference through a tree‐based character reconstruction method, and (3) reconstructed the evolution of range distributions using a dispersal–extinction–cladogenesis model. Results We recovered a new antitropical freshwater clade, Percichthyoidea, composed of Sinipercidae, Percichthyidae (including Percilia but excluding Macquaria colonorum), Elassomatidae and Centrarchidae. Our time‐scale analysis indicates that the Percichthyoidea originated around the Cretaceous–Palaeogene transition. Ancestral habitat reconstructions revealed only one marine‐to‐freshwater transition that preceded the origin of the percichthyoids; the warm‐to‐temperate transition occurred earlier. Ancestral‐area inference indicates a wide‐ranging pan‐American and Eastern Eurasian distribution of the most recent common ancestor of Percichthyoidea. The initial diversification event occurred between the southern (Percichthyidae) and northern (remaining percichthyoids) clades. A second divergence occurred between Eastern Eurasia (Sinipercidae) and North America (Centrarchidae plus Elassomatidae). The trans‐Pacific distribution of the Percichthyidae may have preceded the final breakup of south Gondwana. Main conclusions The present‐day distribution of the Percichthyoidea is unique within extant fishes, comprising four trans‐Pacific continental blocks across the two hemispheres. Current geological and palaeoenvironmental reconstructions may well explain the longitudinal but not the latitudinal pattern of this freshwater fish clade, as it requires a transequatorial freshwater system connecting temperate regions of South and North America during the Late Cretaceous/Palaeogene. An alternative hypothesis is discussed, in which the ancestor of the Percichthyoidea was not completely adapted to freshwater.